2011
DOI: 10.1371/journal.pntd.0001268
|View full text |Cite
|
Sign up to set email alerts
|

Chagasic Thymic Atrophy Does Not Affect Negative Selection but Results in the Export of Activated CD4+CD8+ T Cells in Severe Forms of Human Disease

Abstract: Extrathymic CD4+CD8+ double-positive (DP) T cells are increased in some pathophysiological conditions, including infectious diseases. In the murine model of Chagas disease, it has been shown that the protozoan parasite Trypanosoma cruzi is able to target the thymus and induce alterations of the thymic microenvironment and the lymphoid compartment. In the acute phase, this results in a severe atrophy of the organ and early release of DP cells into the periphery. To date, the effect of the changes promoted by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
94
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 44 publications
(104 citation statements)
references
References 42 publications
8
94
0
2
Order By: Relevance
“…Previous work strongly indicates that part of these immature cells released from the thymus in T. cruzi infected animals is potentially autoimmune, since they have bypassed the classic intrathymic negative selection [5], [40]. More recently, we showed that such a skewed negative selection is not due to an intrinsic defect of the thymic microenvironmental machinery, since thymic epithelial cell function seems normal in terms of AIRE (autoimmune regulator) and tissues restricted antigen gene expression [27]. Accordingly, it is conceivable that the release of immature cells from the thymus into the periphery is rather a cell migration-related disturbance.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Previous work strongly indicates that part of these immature cells released from the thymus in T. cruzi infected animals is potentially autoimmune, since they have bypassed the classic intrathymic negative selection [5], [40]. More recently, we showed that such a skewed negative selection is not due to an intrinsic defect of the thymic microenvironmental machinery, since thymic epithelial cell function seems normal in terms of AIRE (autoimmune regulator) and tissues restricted antigen gene expression [27]. Accordingly, it is conceivable that the release of immature cells from the thymus into the periphery is rather a cell migration-related disturbance.…”
Section: Discussionmentioning
confidence: 76%
“…Such atrophy derives from massive thymocyte depletion, and results in changes in thymocyte export with consequences upon the peripheral T-cell pool and the corresponding T cell repertoire. Previous data strongly indicate that the thymic involution during T. cruzi infection disrupts the homeostasis of the organ, leading to an aberrant output of developing T cells, which likely bypassed intrathymic negative selection events [4], [5], [27], and might be involved in the generation of autoimmunity. Yet, a definitive link between thymic functional abnormalities and the autoimmune events occurring in Chagas disease remains to be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that the atrophy seen in mice who have acute T. cruzi infection is characterized by a loss of DP thymocytes expressing low levels of TCR, together with an abnormal release of immature thymocytes. 60,123,124 Some of these thymocytes have TCR Vβ families, which under normal conditions should have undergone apoptosis, but persist and might, therefore, lead to an autoimmune reaction. 125 The T. cruzi-induced progressive atrophy of the thymus was paralleled by increased circulating levels of glucocorticoids 126 and could be prevented in mice previously adrenalectomized and treated with the glucocorticoid receptor antagonist, RU486.…”
Section: Infection and T-cell Developmentmentioning
confidence: 99%
“…However, regardless of thymic changes promoted by the acute T. cruzi infection, we have showed that the negative selection remains functional [26]. …”
Section: Introductionmentioning
confidence: 99%